CONTRIBUTION TO THE RHIZOGENIC STUDY OF A PERENNIAL POACEE (LYGEUM SPARTUM L.) IN WESTERN ALGERIA - Souhila, Benchenafi-Lachachi; Noury, Benabadji; Fatna, Benabdelmoumen; Djame, Benmansour (European Scientific Journal, ESJ, 2014)
Through this preliminary study, we could follow up the evolution of root fragments of Lygeum spartum L. taken in western region (Algeria). The formation of hair root is the witness of rhizogenesis phenomenon which represents rooting phase. In our experience, the rate of rhizogenesis is different in the two regions and the size of rootlets varies from one station to another. The rate of rhizogenesis is appreciable in nutrient agar whose percentage is 60%. The growth of rootlets is linear in northern regions (Beni-Saf, Zenata). In southern regions, the development is characterized by a more accelerated growth during the second week. The rate of rhizogenesis in the Salmonella schigella environment is about 45% in the stations of Beni-Saf, Zenata and Aouedj, the size evolution of rootlets is always linear but more late.